The association between drug use and mortality in a norwegian prison cohort: a prospective cohort study - Torill Tverborgvik; Marianne Riksheim Stavseth; Anne Bukten (BMC, 2023)
Abstract Background Elevated mortality rates are found among people who have experienced incarceration, even long after release from prison. The mechanisms related to this excess mortality are complex products of both individual and situational factors. The aim of this study was to describe all-cause and cause-specific mortality among people with a history of imprisonment, and to examine both individual and situational factors associated with mortality. Methods In this prospective cohort study we used baseline survey data from the Norwegian Offender Mental Health and Addiction (NorMA) study (N = 733) linked with data from the Norwegian Cause of Death Registry during eight years of follow-up (2013-2021). Results At end of follow-up, 56 persons (8%) of the cohort were deceased; 55% (n = 31) due to external causes such as overdoses or suicides, and 29% (n = 16) to internal causes such as cancer or lung disease. Having a score > 24 on the Drug Use Disorders Identification Test (DUDIT), indicating likely drug dependence was highly associated with external causes of death (OR 3.31, 95% CI 1.34-8.16), while having a job before baseline imprisonment had a protective effect on all-cause mortality (OR 0.51, ,95% CI 0.28-0.95). Conclusions High DUDIT score at baseline were highly associated with external causes of death, even years after the DUDIT screening was done. Screening incarcerated people using validated clinical tools, such as the DUDIT, together with initiation of appropriate treatment, may contribute to reduced mortality in this marginalized population.